(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Current Study Aimed To Know The Level Of The Phenomenon Of Career Alienation Among The Professors Of Human And Social Science Especially To Answer The Basic Questions: - What Is The Level Of The Degree Of Career Alienation With The Professors Of The University Of Ghardaia? - Does The Level Of Career Alienation Differ Among Respondents According To Gender And Age? In Order To Answer These Questions, The Study Was Conducted On All Faculty Members Following The Comprehensive Inventory Method. Data Collection Was Also Based On The Functional Extrapolation Inventory Of Lubna, Thiab (2017). The Analytical Descriptive Method Was Adopted. After Analyzing The Data, The Following Results Were Obtained: - Most Professors Of The Faculty Of Humanities And Social Sciences Have An Average Level Of Career Alienation - There Were No Statistically Significant Differences In The Level Of Feeling Of Career Alienation Among Professors Of Faculty Of Humanities And Social Sciences Attributed To Both Sex And Age Variables. Key Word- Career Alienation , University Teacher, Professional Performance.